Characterizing the microbiota and profiling small non-coding RNAs in the compartments of the equine hindgut - Reed, Kailee Janelle, author; Coleman, Stephen J., advisor; Bruemmer, Jason, committee member; Turk, Phillp, committee member; Bouma, Gerrit, committee member (Colorado State University. Libraries, 2018)
Gastrointestinal homeostasis is a complex relationship that encompasses the host's immune response, physiology, gut structure and the microbes residing within the host. Each one of these has pathways of communication in order to keep the host in a 'healthy state' or homeostasis. While each category has been extensively researched independently, interactions that occur between host and microbe are largely still unknown, especially within the equine species. Because horses are extremely prone to various gastrointestinal diseases, understanding the microbial populations and how the horse might communicate with those populations will provide more insight on equine gut homeostasis. The main objectives were to delineate the microbial structures residing within compartment of the hindgut and to begin to profile gene expression patterns of small RNAs within the same areas. Two different populations of animal subjects were used for the two projects in this thesis: a herd from the University of Kentucky (n=6) and a herd from Colorado State University (n=3). The herd from Kentucky was used for the microbiota data set in order to determine the microbial population structure within the cecum, right ventral colon, right dorsal colon and feces. First, we characterized microbial communities present in each of these anatomical sites and then completed a multivariate model to determine similarities of compartments and compared those to the fecal sample. The population of microorganisms observed in the proximal hindgut appeared similar between cecum and ventral colon, while the dorsal colon and fecal samples appeared to be more alike. Interestingly, there is an anatomical structure separating ventral and dorsal portions of the colon called the pelvic flexure. This could possibly be an indication of the host's contribution of determining the microbial communities in each anatomical region. We also demonstrated that while some microbial signatures from the proximal gut were identified in the feces, the distal gut seemed to be more represented in the fecal sample. The herd from Colorado was used to produce the gene expression data for the second project and the main focus was to profile microRNA (miRNA) expression along the hindgut. These small non-coding RNAs have been identified to be involved in gastrointestinal homeostasis within the intestinal epithelium and are host derived molecules. We demonstrated that each tissue (n=8 for each horse) had unique miRNA expression profiles and these miRNAs identified were used to complete a target pathway analysis which shows possible pathways that could be associated with the biological function of each intestinal site. While each project had different objectives, they are both key players of gastrointestinal homeostasis. For future research, we plan to combine these two areas of study by knowing which miRNA could target specific bacteria residing in the gut, which may further the knowledge of how the host contributes to the population structure of the microbes within their gastrointestinal tracts.
Keywords: equine; microRNA; 16S; molecular biology; microbiota